The Establishment of ADA School of Medicine as Part of ADA Growth Strategy - Huseynova, Aytakin (ADA University, 2019)
From its inception, University established new programs on undergraduate and graduate levels to grow further and become a world-class university. As a public university, new program launching was aligned to the mission and vision of ADA and served the needs of the country to develop human capital. From the modest partnership with the Information Technologies University a decade ago, to today’s complex of public, private and international collaborations, the academic programs’ profile of ADA University has evolved immensely. However, desire to tap new market segments in order to explore new opportunities in higher education through alliances and collaborations with local and international partners remains severe. Today ADA University’s mission is not only to provide qualitative education, but also to grow as an international brand, to be competitive in the market of higher education and raise value proposition of qualitative education in different fields. In an effort to help ADA University to enhance competitive advantage and to reveal hidden potential and capacity, this project proposes a new School of Medicine establishment as a way to grow and to build a strong brand image as multi-profiled university.
Keywords: Business; Medicine program.; Medical program -- Azerbaijan.; Undergraduate education.; Undergraduate education -- Azerbaijan.; ADA University -- Azerbaijan.